Implementing molecular dynamics simulation on the Sunway TaihuLight system with heterogeneous many‐core processors. (10th April 2018) - Dong, Wenqian; Li, Kenli; Kang, Letian; Quan, Zhe; Li, Keqin
Summary: In various research of atom and molecule physical movements, molecular dynamics (MD) simulation is a common tool to simulate and investigate the real molecular motion. However, it introduces a significant penalty in performance, power, electricity, and running time. Consequently, once the simulation size scales up and computing demands keep growing, it comes at substantial costs in performance and energy usage. In this paper, an optimized MD implementation on the Sunway TaihuLight supercomputer with heterogeneous many‐core processors is developed to address the abovementioned issues. The Sunway TaihuLight is a totally independently designed and developed Chinese supercomputer with a profusely customized integration approach and a brand new many‐core processor, the SW26010. The computing power mainly supported by the homegrown many‐core SW26010 processors differs from other existing heterogeneous supercomputers. The Sunway TaihuLight is a heterogeneous supercomputer that ranks first in the world with its peak performance over 100 PFLOPS. Firstly, we propose a new algorithm based on cluster particles to fit the special architecture of SW26010. Then, three optimization methods of the MD simulation are implemented step by step: parallelized extensions to SW26010, memory‐access optimizations, and vectorization. After these optimization processes, a 14x speedup is achieved on a single computing node and yields significant performance and energy improvements. Superiorly, almost 24, 000 computing nodes (6, 000, 000 cores) are applied in our experiments, which gain an almost linear speedup. Besides, the proposed methods also can be adapted and fit to other molecular dynamics codes, even other similar scientific applications.